Soundscapes - Olszewska, Marta (Journal of Education Culture and Society, 2020)
This article examines the issues of soundscape construction and reception and states that a city is a construction built from private sonic narrations that both shape and are shaped by spatial structures. The analysis of three audio-visual practices: Playtime,a film by Jacques Tati;Infrasonic Soundscape, an interactive online artwork by Hidekazu Minami; and Dialtones (A Telesymphony) by Golan Levin, a concert performance whose sounds were produced by theaudience’s mobile phones reveals the polyphonic character of space. These examples necessitate verifying the way one perceives the understanding of the concepts of sound and space as well as their interactions. The phenomenon of soundscapes requires transgressing the dichotomies of space/place, seeing/listening (sound/image), and listener (recipient)/creative subject (sender of a specific message), in favour of the intermediate categories. The core of the interspace which arises on this ground constitutes a dialog anyone might enter if they afford a gesture addressed to the other (various forms of space embodiment).